Part 1: Synthesis and characterization of magnetic Cr5Te8 nanoparticles. Part 2: Local atomic structure studies using theory to simulate polarons in superconducting cuprates and experiment to analyze alternative energy nanomaterials - Martucci, Mary B., author; Prieto, Amy L., advisor; Elliott, C. Michael, committee member; Fisher, Ellen R., committee member; Rickey, Dawn, committee member; Patton, Carl E., committee member (Colorado State University. Libraries, 2012)
The field of spintronics, the development of spin-based devices that utilize the spin degree of freedom to increase memory capacity, has emerged as a solution to faster more efficient memory storage for electronic devices. One class of materials that has been extensively studied is the half-metallic ferromagnets, compounds that are 100% spin-polarized at the Fermi level. One material in this group that has been investigated is chromium telluride (Cr1-xTe), whose family of compounds is known to exhibit a wide range of interesting magnetic and electronic properties. We have developed a hot injection solution synthesis of Cr5Te8 nanoplatlets which show similar magnetic behavior to the bulk material. It has also been shown that selenium and sulfur analogues can be obtained without changing the reaction conditions, making progress toward a better understanding of the reaction as well as an interesting family of compounds. Using real-space simulations, the effect of polarons in the high-Tc superconducting cuprates has been studied. The simulations demonstrate energetically favorable sites for the defects and show evidence of longer-range pairing interactions. Variations of the stripe show similar energetic results. X-ray absorption fine structure spectroscopy and neutron scattering have been utilized to examine the local structure of Ni-doped Mg nanoparticles, a hydrogen storage material as well as Cu2ZnSnS4 (CZTS) nanoparticles, a photovoltaic material. The Mg-Ni material shows much local disorder upon hydrogen cycling. The CZTS data demonstrate a loss of sulfur from around the copper sites upon annealing, helping to explain the changes observed in the optical absorption properties resulting from the annealing process.
Synthesis and characterization of magnetic Cr5Te8 nanoparticles
Local atomic structure studies using theory to simulate polarons in superconducting cuprates and experiment to analyze alternative energy nanomaterials
Keywords: local structure; nanoparticle